Cystic cervical lymph nodes metastasis revealing a papillary carcinoma of the thyroid gland: A case report - Diouf MS; Thiam A; Maïga S; Deguenonvo REA; Diop A; Barry MW; Diouf R (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Cystic cervical lymph nodes are a rare anatomo-clinical form. They are a typical presentation of metastasis of cancers of the waldeyer ring in particular those of the palatine tonsil. Nevertheless, they may reveal a papillary carcinoma of the thyroid even though the thyroid gland is clinically normal. In this case the combination of ultrasound and fine needle aspiration cytology (FNAC) with intranodal thyroglobulin dosage allows to differentiate lymphadenopathies of thyroid origin from other causes. We report the case of a 40-year-old patient received in December 2015 in our hospital for cystic cervical lymph nodes without clinical thyroid mass. FNAC was for a metastasis of an adenocarcinoma. Pan endoscopy was normal. A lymph node biopsy was performed and the histology returned in favor of metastasis of papillary adenocarcinoma of the thyroid gland. The patient had undergone a cervicotomy with total thyroidectomy, left modified radical neck dissection and right functional lymphadenectomy. The histology of the surgical specimen confirmed the diagnosis of papillary carcinoma of the thyroid gland with cystic lymph node metastasis. This clinical case highlights the diagnostic approach of cystic cervical lymph node metastasis.